2019
DOI: 10.1186/s12871-019-0904-6
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the relationship between postoperative urine output and one year transplanted kidney function

Abstract: Background: Kidney transplantation (KT) is the most obvious method of treating a patient with end-stage renal disease. In the early stages of KT, urine production is considered a marker of successful reperfusion of the kidney after anastomosis. However, there is no clear conclusion about the relationship between initial urine output after KT and 1-year renal function. Thus, we investigated the factors that affect 1-year kidney function after KT, including urine output. Methods: This retrospective study investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Our study also showed that urinary output was superior to serum creatinine in predicting short-term mortality of elderly patients with ARF. Although the assessment of AKI stage is not necessarily based on urine volume, the initial postoperative urine volume was considered an accurate predictor of delayed graft function ( Kim et al, 2019 ). The reduction of urinary output can be attributed to insufficient blood flow to the kidneys, due to reduced blood volume and systolic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that urinary output was superior to serum creatinine in predicting short-term mortality of elderly patients with ARF. Although the assessment of AKI stage is not necessarily based on urine volume, the initial postoperative urine volume was considered an accurate predictor of delayed graft function ( Kim et al, 2019 ). The reduction of urinary output can be attributed to insufficient blood flow to the kidneys, due to reduced blood volume and systolic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that urinary output was superior to serum creatinine in predicting short-term mortality of elderly patients with ARF. Although, the assessment of AKI stage is not necessarily based on urine volume, the initial postoperative urine volume was considered an accurate predictor of delayed graft function [14]. The reduction of urinary output can be attributed to insu cient blood ow to the kidneys, due to reduced blood volume and systolic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Recipients of DCD kidneys are capped at 20%, as some studies have shown that DCD kidneys may be prone to worse outcomes, 31 , 32 , 33 though this observation remains controversial. 34 , 35 Although differing outcomes across studies may be due to magnitude of ischemic reperfusion injury, generally greater in DCD kidneys, versus the increased propensity for repair, generally improved in the typically younger DCD donor organs, we sought to approximate current clinical practice by the cap on DCD kidneys. Kidneys may be preserved by static cold storage or cold pulsatile machine perfusion, with the latter capped at 40% to reflect current practice as quantified in the Organ Procurement and Transplantation Network (OPTN) database.…”
Section: Methodsmentioning
confidence: 99%
“…No serious adverse events were assessed as related to study drug. have shown that DCD kidneys may be prone to worse outcomes [31][32][33] , though this observation remains controversial 34,35 . While differing outcomes across studies may be due to magnitude of ischemic reperfusion injury, generally greater in DCD kidneys, versus the increased propensity for repair, generally improved in the typically younger DCD donor organs, we sought to In the Phase 2 trial, both eGFR and graft failure had effect sizes sufficient to reach statistical significance.…”
Section: The Role Of Hgf and Ang-3777 In Kidney Repairmentioning
confidence: 99%